Sustainable fertilization of vegetable crops in the highland of Lembang, West Java, Indonesia: Findings from a pilot with vegetable farmers using dairy cattle manure - Putter, Herman de; Vries, Marion de; Adiyoga, Witono; Suharyono, Deni; Gunadi, Nikardi (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
Sustainable fertilization can increase income of farmers and reduce environmental pollution. Farmers should learn to align fertilizer use with crop requirements and soil fertility. Organic manures should be applied first, whereafter chemical nitrogen and potassium fertilizers should be used to complement nutrient requirements. Phosphate levels in soils in Lembang are high and limit the use of manure. Cow manure is a good source of nutrients and organic matter in vegetable crops and can lower environmental pollution in case of weight-based replacement of chicken manure.